RELAÇÕES DE DEPENDÊNCIA ENTRE OS FLUXOS DE TRABALHO, MATERIAIS E EQUIPAMENTOS NO CANTEIRO DE OBRAS DE EDIFÍCIOS ALTOS - Fazinga, Wanessa; Pescuma, Vinicius Jordão; Saffaro, Fernanda Aranha (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
One of the management challenges in construction is to maintain the continuity of the production flow under the process and operations perspectives. There are difficulties in keeping in sync between labor flows, referring to the performance of the labor resource, and the input flows, feed of materials and equipment. This article aims to describe the relationships of interdependence between these flows. The empirical investigation was conducted through a study case carried out in the execution of the reinforced concrete structure of a multi-storey building. The results have indicated that the flow of inputs can occur disconnected from the workflow, resulting in loss of capacity or production interruptions. The need to improve the means of communication among workers involved in the production proved to be essential to allow the flow of inputs and the continuity of the workflow.